Successful management of a rare case of juvenile giant right ventricular myxoma - Gong, Ke; Yang, Yifeng; Shen, Yadan; Liu, Haidan; Xie, Li; Liu, Jijia (Frontiers in Surgery, 2023)
Primary cardiac tumors are extremely uncommon in young children and infants. Cardiac myxoma are typically found in the atria, predominately in the left atrium, with relatively few found on the right side, such as in the right ventricle or pulmonary artery. Numerous significant complications, including sudden death, can result from obstruction of the main pulmonary artery trunk and right ventricular outflow tract. Here, we describe the case of a 14-year-old Chinese girl diagnosed with a right ventricular myxoma located in the right ventricle and extended into the main pulmonary trunk. Complete resection of the myxoma and histological confirmation were performed.